A The Influence of Muslim-Friendly Tourism, Brand Image, and Services on the Decision to Choose Hajj and Umrah Travel through Trust: The Influence of Muslim-Friendly Tourism, Brand Image, and Services on the Decision to Choose Hajj and Umrah Travel through Trust - shofia, ulya; Mochlasin (Journal of Sharia Economic Law, 2025)
This study aims to investigate the influence of Muslim-friendly tourism, brand image, and service on decisions to choose Hajj and Umrah travel services, with trust as a variable of interest (a case study of pilgrims from PT Baitullah Bawean Hajj Umrah School). This type of research is quantitative, focusing on the consumer population of the Baitul Bawean hajj school. The data obtained is then processed using a tool and further analyzed with the help of IBM SPSS 21. The result of what have been obtained from this study explain that the results of this research test show that muslim friendly tourism has a positive and significant influence on the decision, brand image has a positive and significant effect on the decision, service has a positive and significant effect on the decision, musim friendly tourism, brand image, and service has a positive and significant effect on the purchase decision through trust. the influence of muslim-friendly tourism, brand image, and services on the decision to choose hajj and umrah travel through trust.